Morphological and molecular assessment of genetic diversity in some yam (dioscorea species) landreaces - Alarape, S.A. (University of Ibadan, 2021)
Yam (Dioscorea species) consist of about 600 species with only 6 species mostly used as food yam. New landraces have been cultivated across Sub-Saharan Africa with little or no information on their identities. However, information on these landraces will serve as a genetic tool for crop improvement. This study assesses the morphological and molecular characterisation of the newly collected yam landraces for genetic diversity.One hundred accessions, comprising Dioscorea rotundata (83), Dioscorea abyssinica (16) and Dioscorea cayenensis (1) sourced from Benin Republic were planted in a Randomized Complete Block Design replicated twice, in Ibadan during the 2018 cropping season. Data were recorded on quantitative and qualitative traits and were subjected to Principal Component Analysis (PCA), Cluster Analysis (CA), and a total of 13,338 DArTseq-SNP markers were used to reveal the pattern of genetic diversity within the accessions. All traits contribute to the first three principal component which account for 66% of the observed phenotypic variation. The accessions were grouped into four phenotypically distinct clusters with members of the cluster having high phenotypic similarities. Heterozygosity values of the SNPs ranged from 0.00 to 0.75 with mean of 0.03.The maximum distance root was 0.15, while the branch length ranges from 5.8x10-5 to 10.13 in the cladogram tree. Principal component analysis based on the SNP markers showed that the three component axes contributed 36.4% of the total genetic variance observed in the accessions. The genetic relationship shows that all the accessions were clustered in five different groups according to their geographical sources. The most diverse accessions were TDr-5260 with the longest spines, TDr-5193 with the highest number of leaves and tuber width, TDr-5262 had the largest leaf width while TDc-4695 had the longest petiole length.There was a high morphological variation in the accessions studied. The low heterozygosity of SNP markers observed in this study further buttress the self-pollinating nature of yam.